2017
DOI: 10.3390/fermentation3040054
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Volatile Fatty Acids from Microalgae for the Production of High Added Value Compounds

Abstract: Volatile Fatty Acids (VFA) are small organic compounds that have attracted much attention lately, due to their use as a carbon source for microorganisms involved in the production of bioactive compounds, biodegradable materials and energy. Low cost production of VFA from different types of waste streams can occur via dark fermentation, offering a promising approach for the production of biofuels and biochemicals with simultaneous reduction of waste volume. VFA can be subsequently utilized in fermentation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 83 publications
1
23
0
Order By: Relevance
“…It is understood that algae possess isocitrate lyase and malate synthase, enzymes necessary to carry out the glyoxylate cycle [30]. The glyoxylate cycle plays an essential role in acetate metabolism and also allows for bypass of OGDH.…”
Section: Impacts Of Thiamine and Hmp On Algal Central Metabolism In Amentioning
confidence: 99%
“…It is understood that algae possess isocitrate lyase and malate synthase, enzymes necessary to carry out the glyoxylate cycle [30]. The glyoxylate cycle plays an essential role in acetate metabolism and also allows for bypass of OGDH.…”
Section: Impacts Of Thiamine and Hmp On Algal Central Metabolism In Amentioning
confidence: 99%
“…Few studies on the cultivation of thraustochytrids using single VFA as carbon source have been attempted so far; only C. cohnii has been proposed for the production of lipids ( Chalima et al, 2017 ). The oleaginous thraustochytrid Aurantiochytrium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Study on lipogenesis by oleaginous microalgae and yeast cultivated on single VFA as well as on the mixture of VFAs are extensively studied for biofuel production ( Xia and Murphy, 2016 ; Llamas et al, 2020 ). PUFA production by marine microalga Crypthecodinium Cohnii cultivated on mixture of VFAs is also an explored topic ( Chalima et al, 2017 ), but to the best of our knowledge this is the first attempt to cultivate an oleaginous marine thraustochytrids using a mixture of VFAs as carbon source. Moreover, in this study, five oleaginous microorganisms were selected to cultivate on VFAs produced through anaerobic digestion of food mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al reported that Thraustrochytrium aureum 28210 can reach 48.3-58.2% of DHA of total fatty acids [83]. Lee Chang et al reported results of 41-75% of DHA of total fatty acids for Thraustrochytrium aureum 38304 strain -and 5-13% of DHA for ulkenia [84]. In a recent report, the main PUFA producer's growth under heterotrophic conditions were reviewed by Chalima et al [85].…”
Section: Heterotrophic Microalgae For Omega-3 Polyunsaturated Fatty Acids Productionmentioning
confidence: 99%